2014
DOI: 10.1128/jvi.01901-14
|View full text |Cite|
|
Sign up to set email alerts
|

An Eriophyid Mite-Transmitted Plant Virus Contains Eight Genomic RNA Segments with Unusual Heterogeneity in the Nucleocapsid Protein

Abstract: Eriophyid mite-transmitted, multipartite, negative-sense RNA plant viruses with membrane-bound spherical virions are classified in the genus Emaravirus. We report here that the eriophyid mite-transmitted Wheat mosaic virus (WMoV), an Emaravirus, contains eight genomic RNA segments, the most in a known negative-sense RNA plant virus. Remarkably, two RNA 3 consensus sequences, encoding the nucleocapsid protein, were found with 12.5% sequence divergence, while no heterogeneity was observed in the consensus sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 42 publications
4
111
0
Order By: Relevance
“…RLBV, FMV, PPSMV, PPSMV 2 and HPWMoV have been shown to encode a 'P5' protein of between 55 and 59 kDa, and HPWMoV P6 is also of this size. Indeed, HPWMoV P5 has low but detectable amino acid sequence similarity to the RLBV, FMV and PPSMV P5 proteins (Tatineni et al, 2014); however, their sequences provide no information about the possible function of any of these proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RLBV, FMV, PPSMV, PPSMV 2 and HPWMoV have been shown to encode a 'P5' protein of between 55 and 59 kDa, and HPWMoV P6 is also of this size. Indeed, HPWMoV P5 has low but detectable amino acid sequence similarity to the RLBV, FMV and PPSMV P5 proteins (Tatineni et al, 2014); however, their sequences provide no information about the possible function of any of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Other, tentative, members of the genus Emaravirus are Pigeonpea sterility mosaic virus (PPSMV), Pigeonpea sterility mosaic virus 2 (PPSMV 2), Redbud yellow ringspot-associated virus (RYRSaV), High Plains wheat mosaic virus (HPWMoV), Wooly burdock yellow vein virus (WBYVV), Viburnum line pattern-associated virus (VibLPaV) and Blackberry leaf mottle-associated virus (BLMaV). Although not all of these viruses have been studied in the same detail, they all have multi-segmented genomes of (probably) negative-strand RNA, some are known to have roughly spherical particles enclosed in a double-membrane envelope and all have similarity in the amino acid sequences of some of their encoded proteins (Ebrahim-Nesbat & Izadpanah, 1992;Elbeaino et al, 2009Elbeaino et al, , 2014Elbeaino et al, , 2015Laney et al, 2011;Sabanadzovic & Abou Ghanem-Sabanadzovic, 2011;Bi et al, 2012;Ishikawa et al, 2012;Tatineni et al, 2014). Other shared attributes are their transmission between plants by eriophyid mites (Mielke-Ehret & Mühlbach, 2012), and the presence of short conserved, imperfectly repeated nucleotide sequences at the 59 and 39 termini of the viral RNAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in this journal, Tatineni et al (1) mistakenly reported HPV as being present in New Zealand, citing the paper by Lebas et al from 2005 (2). The 2005 report clearly states that New Zealand is HPV free in both the abstract and the introduction (2).…”
mentioning
confidence: 99%
“…This mite also vectors two other viruses in wheat in the Great Plains: Wheat mosaic virus (WMoV), also known as High Plains virus, a tentative member of the genus Emaravirus (Seifers et al 1997;Tatineni et al 2014); and Triticum mosaic virus (TriMV; Poacevirus, Potyviridae) (Seifers et al 2009;Tatineni et al 2009). These three wheat viruses are widely spread across the Great Plains; however, WSMV has been shown to be the predominant virus in this complex (Burrows et al 2008;Byamukama et al 2013).…”
mentioning
confidence: 99%